Utilização de fibras de celulose e tanino gálico na elaboração de vinho branco proveniente de uvas com Botrytis cinerea - Carraro, Jean Carlos (My University, 2024)
Serra Gaúcha has an excellent oenological capacity to produce quality still white wines. However, due to the occurrence of natural phenomena in Rio Grande do Sul, excess precipitation and humidity favors the emergence of diseases directly in the bunches, resulting in a drop in production, poor health in the grapes and loss of quality of the grapes and wine. . Botrytis cinerea is a fungus that causes gray rot in grapes and is present in all vineyards around the world. This study aimed to evaluate the use of cellulose fibers to reduce the negative effects caused by Botrytis cinerea in musts and wines from Chardonnay grapes (Vitis vinifera L.) and contribute to the development of a new technology to improve the quality of wines. whites. The effects of cellulose fibers were compared with a commercial gallic tannin recommended for the same purpose. This commercial gallic tannin has a considerably higher purchase price than cellulose, around 65% more expensive. The experiment consisted of eight treatments and three replications with different doses of each product. The musts and wines obtained were analyzed for basic composition, volatile compounds, color index and phenolic compounds, according to the official Brazilian methodology, and the resulting wines were sensorially evaluated by a team of twelve qualified tasters. The presence of rot caused by Botrytis cinerea altered the composition of the musts and the quality of the wines obtained. The musts obtained from rotten grapes (T2) showed the highest levels of volatile acidity and gluconic acid due to the action of oxidative enzymes present in the fungus. Both the use of gallic tannin and cellulose fiber were efficient in reducing the volatile acidity levels of the must, presenting lower values than the must with untreated rot (T2). The addition of 1.5 g.Kg-1 of cellulose fibers (T8) resulted in the lowest concentrations of acids coumaric and epicatechin in wines. Few variations were found between the wines obtained in terms of fatty acid analysis. However, regarding sensory characteristics, wines obtained from healthy untreated grapes (T1) exhibited a general trend of greater positive intensity, clarity and quality, a fact that is justified by the quality of the grape being linked to better acceptance of the final product. However, the use of cellulose fibers (T6, T7 and T8) favored the results of the vinification of white Chardonnay grapes with Botrytis cinerea, mitigating its negative effects, and proved to be more effective than the use of commercial gallic tannin, approaching the values obtained from healthy grapes in the global assessment of sensory analysis. [resumo fornecido pelo autor]
A Serra Gaúcha apresenta uma excelente capacidade enológica para produzir vinhos brancos tranquilos de qualidade. Porém, devido à ocorrência de fenômenos naturais, no Rio Grande do Sul, o excesso de precipitações e de umidade favorece o surgimento de doenças diretamente nos cachos, resultando em queda da produção, deficiência sanitária da uva e perda de qualidade da uva e do vinho. O Botrytis cinerea é um fungo causador da podridão cinzenta da uva e está presente em todos os vinhedos do mundo. Este estudo teve como objetivo avaliar a utilização de fibras de celulose para a redução dos efeitos negativos causados pelo Botrytis cinerea em mostos e vinhos provenientes de uva Chardonnay (Vitis vinifera L.) e contribuir para desenvolvimento de uma nova tecnologia para melhorar a qualidade dos vinhos brancos. Foi comparado os efeitos das fibras de celulose com um tanino gálico comercial recomendado para o mesmo fim. Este tanino gálico comercial tem valor de aquisição consideravelmente mais elevado que a celulose, em torno de 65% mais caro. O experimento consistiu de oito tratamentos e três repetições com diferentes doses de cada produto. Os mostos e vinhos obtidos foram analisados quanto à composição básica, compostos voláteis, índice de cor e compostos fenólicos, conforme a metodologia oficial brasileira, e os vinhos resultantes avaliados sensorialmente por uma equipe de doze degustadores qualificados. A presença de podridão causada pelo Botrytis cinerea alterou a composição dos mostos e a qualidade dos vinhos obtidos. Os mostos obtidos de uvas com podridão (T2) apresentaram os maiores níveis de acidez volátil e ácido glucônico devido à ação das enzimas oxidativas presentes no fungo. Tanto a utilização de tanino gálico como a de fibra de celulose foram eficientes para a redução dos níveis de acidez volátil do mosto, apresentando valores inferiores ao mosto com podridão sem tratamento (T2). A adição com 1,5 g.Kg-1 de fibras de celulose (T8) resultou nas menores concentrações de ácidos cumárico e epicatequina nos vinhos. Poucas variações foram encontradas entre os vinhos obtidos quanto às análises dos ácidos graxos. Entretanto, quanto às características sensoriais, os vinhos obtidos de uvas sadias sem tratamento (T1), exibiram uma tendência geral de maior intensidade positiva, nitidez e qualidade, fato que se justifica pela qualidade da uva estar ligada à melhor aceitação do produto final. Porém a utilização de fibras de celulose (T6, T7 e T8) favoreceu os resultados da vinificação de uvas brancas Chardonnay com Botrytis cinerea, amenizando seus efeitos negativos, e demonstra-se mais eficaz que o uso de tanino gálico comercial, aproximando-se dos valores obtidos de uvas sãs na avalição global da análise sensorial. [resumo fornecido pelo autor]
Keywords: Vitivinicultura; Uva; Vinho; Fungos; Viticulture; Grapes; Wine; Fungi